2017
DOI: 10.3389/fphar.2017.00631
|View full text |Cite
|
Sign up to set email alerts
|

Binase Immobilized on Halloysite Nanotubes Exerts Enhanced Cytotoxicity toward Human Colon Adenocarcinoma Cells

Abstract: Many ribonucleases (RNases) are considered as promising tools for antitumor therapy because of their selective cytotoxicity toward cancer cells. Binase, the RNase from Bacillus pumilus, triggers apoptotic response in cancer cells expressing RAS oncogene which is mutated in a large percentage of prevalent and deadly malignancies including colorectal cancer. The specific antitumor effect of binase toward RAS-transformed cells is due to its direct binding of RAS protein and inhibition of downstream signaling. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Zeolite-based nanoparticles used in generating time-controlled release of 5-fluorouracil from zeolite preparations showed anti-cancer effect toward Caco-2 monolayers (Spanakis et al, 2014). Earlier, we have demonstrated that binase-halloysite complex doubled anticancer efficiency of binase due to its perfect absorption by cells and longer release reducing the viability of human colon adenocarcinoma cells Colo320 by 60% (Khodzhaeva et al, 2017). The same level of toxicity toward human adenocarcinoma Caco2 cells was obtained for chabazite-binase complex.…”
Section: Discussionmentioning
confidence: 98%
“…Zeolite-based nanoparticles used in generating time-controlled release of 5-fluorouracil from zeolite preparations showed anti-cancer effect toward Caco-2 monolayers (Spanakis et al, 2014). Earlier, we have demonstrated that binase-halloysite complex doubled anticancer efficiency of binase due to its perfect absorption by cells and longer release reducing the viability of human colon adenocarcinoma cells Colo320 by 60% (Khodzhaeva et al, 2017). The same level of toxicity toward human adenocarcinoma Caco2 cells was obtained for chabazite-binase complex.…”
Section: Discussionmentioning
confidence: 98%
“…The size and shape of nanoparticles will affect the adsorption patterns, protein structure, and function. Many enzymes, such as lysozyme [ 70 ], lipase [ 71 , 72 ], nattokinase [ 73 ], asparaginase [ 74 ], SOD [ 75 , 76 ], β-galactosidase [ 77 ], glucocerebrosidase [ 78 ], binase [ 79 ], hyaluronidase (HAses) [ 80 ], GOX, and HRP [ 69 ], have been reported to be immobilized onto nanoparticles. Among these enzymes, the activity and stability of glucocerebrosidase are compromised in patients with Gaucher disease (metabolic storage disorder) because these patients do not properly degrade glucosylceramide (GlcCer), which accumulates and can lead to health problems, including bone lesions.…”
Section: Immobilization Of Therapeutic Enzymesmentioning
confidence: 99%
“…In addition to siRNA, ribonucleases (RNases) have also been proposed in anticancer therapy since they may destroy RNA in cancer cells and produce signals leading to cancer cells’ programmed death. Khodzhaeva et al [ 76 ] immobilized Bacillus pumilus RNase-binase-on HNTs. Cytotoxicity studies toward human colon adenocarcinoma Colo320 confirmed that while the cells’ viability after 24 h incubation with pristine HNTs was as high as 97%, the free binase and binase-loaded HNTs reduced the number of viable cells by 27% and 64%, respectively.…”
Section: Interactions Of Hnts and Hnts-based Systems With Cancer Cellsmentioning
confidence: 99%